PENINGKATAN PEMAHAMAN MODEL BARU PEMBIAYAAN PEMILIKAN RUMAH MELALUI MODEL MUSYĀRAKAH MUTANĀQISHAH DALAM PERSPEKTIF AL-QUR’AN DI MASJID AN-NUR BABELAN BEKASI - Nur Arfiyah Febriani; Amiruddin Kuba; M. Suaib Tahir; Devy Meris Rowanti; Moh. Mauludin (MADANI Abdimas : Jurnal Penelitian dan Pengabdian Masyarakat, 2023)
The focus of this research aims to find out more about the home ownership financing model (PPR) through the musyārakah mutanāqishah model or what is known as the MMQ model. In several sharia economic literatures, there are several PPR models, but the author is more interested in researching the MMQ PPR model. The advantage of the MMQ model is that it presents an equal partnership pattern between customers and banks. This is in line with sharia banking entities which are synonymous with profit and loss sharing (PLS). The MMQ model is also considered a solution innovation product with a financing pattern that is more affordable, fairer, and more compliant with sharia principles. However, its application to sharia financial institutions and banking is not yet fully in accordance with the provisions. This MMQ model is still debatable among Islamic economics experts and academics. Nevertheless, the majority of them agree and support this MMQ model. This research will analyze using qualitative methods and maudu'ī interpretation to explore the MMQ concept in the Al-Qur'an more comprehensively